Zingerone alleviates inflammatory pain by reducing the intrinsic excitability of anterior cingulate cortex neurons in a mice model - Yuanyuan Wang; Yuanyuan Wang; Yuanyuan Wang; Lang Dong; Lang Dong; Shu Han; Yuehan You; Mingrui Zhang; Bingjing Sun; Bingjing Sun; Hong Ni; Hong Ni; et al. (Frontiers in Pharmacology)
BackgroundZingiber officinale Roscoe has been shown to possess analgesic properties. Zingerone (ZO), a bioactive compound derived from Zingiber officinale Roscoe, exhibits a range of pharmacological effects, including anti-inflammatory, anti-cancer, antioxidant, antibacterial, and anti-apoptotic activities. However, the analgesic properties of zingerone remain unclear.MethodsComplete Freund’s adjuvant (CFA) was administered to the left hind paw of C57BL/6 mice to induce a model of inflammatory pain. The analgesic effects of zingerone were assessed using the Von Frey and Hargreaves tests. In vivo fiber photometry and whole-cell patch clamp techniques were employed to investigate the potential mechanisms.ResultsBoth acute and long-term treatment with zingerone resulted in a significant increase in mechanical and thermal pain thresholds in mice experiencing CFA-induced inflammatory pain. Mechanical stimulation led to a pronounced increase in calcium levels within the anterior cingulate cortex (ACC) neurons of the inflammatory pain model, which was alleviated by zingerone administration. Furthermore, zingerone was found to modify synaptic transmission to ACC neurons and decrease their intrinsic excitability by prolonging the refractory period of these neurons.ConclusionZingerone demonstrates potential for alleviating CFA-induced inflammatory pain by reducing the intrinsic excitability of ACC neurons in a mouse model.